2009
DOI: 10.1007/s11204-009-9052-1
|View full text |Cite
|
Sign up to set email alerts
|

Performance analysis of seismic-insulating kinematic foundations on support elements with negative stiffness

Abstract: The installation of seismic-insulating systems is one of the most effective methods of earthquake protection of buildings and structures in highly seismic-prone regions. A sizable number investigations and monographs are devoted to problems of the analysis, design, and practical application of such systems [1,2,3,4]. Currently, however, many important problems of the theory of seismic-insulating systems are under discussion, and design solutions are occasionally incorrect. Examples of this kind of errors are b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 1 publication
(1 reference statement)
0
26
0
Order By: Relevance
“…Some of these systems were practically implemented in real buildings [1], [2], [4], [5], making it possible to assess their workability for building industry. Vibration tests were carried out at many facilities [6], [7], which provided experimental data on the behavior of these systems under dynamic impacts. However, essentially all developed systems need additional analysis under full-scale conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these systems were practically implemented in real buildings [1], [2], [4], [5], making it possible to assess their workability for building industry. Vibration tests were carried out at many facilities [6], [7], which provided experimental data on the behavior of these systems under dynamic impacts. However, essentially all developed systems need additional analysis under full-scale conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, a plethora of papers on rocking structures has been published studying these structures theoretically [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] and experimentally. This application is usually termed "kinematic isolation" [50][51][52][53][54][55] : The bottom floor comprises rocking concrete rocking columns and is essentially an intentionally designed soft story with large displacement capacity. [44][45][46][47][48][49] What has received less attention in the literature published in English is that rocking has been used in the USSR since 1960s (and is still used in former USSR states) as a seismic response modification technique for buildings.…”
Section: Introductionmentioning
confidence: 99%
“…[44][45][46][47][48][49] What has received less attention in the literature published in English is that rocking has been used in the USSR since 1960s (and is still used in former USSR states) as a seismic response modification technique for buildings. This application is usually termed "kinematic isolation" [50][51][52][53][54][55] : The bottom floor comprises rocking concrete rocking columns and is essentially an intentionally designed soft story with large displacement capacity. 55 The uplift of the soft story columns acts like a mechanical fuse and limits the seismic forces transmitted to the superstructure.…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that the "slit-plate" damper can dissipate the energy input by severe earthquakes in frames with rocking columns, with limited damage; hence the significance of the proposed damage index E m to avoid replacing the dampers after a severe earthquake. Rocking structures have been investigated since the 1970s [17][18][19][20][21][22][23] and have evolved in two directions [24]. One direction, developed mainly in Russia (or the USSR), stems from the concept of "kinematic support" [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Rocking structures have been investigated since the 1970s [17][18][19][20][21][22][23] and have evolved in two directions [24]. One direction, developed mainly in Russia (or the USSR), stems from the concept of "kinematic support" [20][21][22][23]. The rocking structure dealt with in this paper is in line with the other direction, developed mainly in the USA [17,18] and New Zealand [19], and is shown in Figure 2a.…”
Section: Introductionmentioning
confidence: 99%